Anadolu’da Harp Yılları, Hilal-i Ahmer Mecmuası ve Dönemin Toplumsal Sorunları / War Years in Anatolia, Red Crescent Society and Social Problems of that Period</i - KORKUT, HASAN (Journal of History Culture and Art Research, 2013)
Öz 1863’de kurulan Osmanlı Hilal-i Ahmer Cemiyeti Balkan ve Birinci Dünya Savaşları’nda önemli vazifeler ifa etti. 1911-1921 arası dönem Hilal-i Ahmer Cemiyeti açısından çok önem arz etmektedir. Trablusgarp Savaşı ile başlayıp Birinci Dünya Savaşı ile sonuçlanan dönemde Osmanlı Hilal-i Ahmer Cemiyeti Osmanlı askeri kurumlarıyla işbirliği içinde önemli vazifeler görmüştür. Gerek cephedekilere ve gerek cephe gerisinde kalanlara, özellikle yaşlı, kadın ve çocuklara yaptığı yardımlar ile dönemin kanayan yaralarına merhem oldu. Esirlerle ve muhacirlerle ilgili meseleler ile çok yakından ilgilendi. Ayrıca Cemiyet toplumsal felaketler, yaygın hastalıklar ve hıfzıssıhha alanında halka önemli yardımlarda bulunmuştur. Abstract The Ottoman Red Crescent Society was established in 1863 and it carried out important functions during the Balkan and First World Wars. The period of 1911-1923 was a crucially important era for the Ottoman Red Crescent. In a period of continuing wars starting with the War of Tripoli and lasting until the end of the First World War, the Ottoman Red Crescent worked in close collaboration with the Ottoman military establishment. In addition to opening hospitals to the wounded, it also handled the complicated case of the prisoners of war. Besides these fundamental tasks, the Ottoman Red Crescent had also performed a variety of activities such as significant assistances by establishing accommodation to the refugees, women and old people. The Ottoman Red Crescent also supported population against the social disasters, common diseases and health issues.